Network Planning Location Model for China Railway Express. Issue 2 (February 2019) - Wu, Yuehui; Lin, Chang; Huang, Jingyu
With the gradual implementation of the Belt & Road Initiative, China Railway Express (CRExpress) has gradually gained support as an important transportation mode between China and Europe. However, the high cost of operation, caused by the unscientific organization mode and the small quantity of returning cargo, hinders the further development of CRExpress. Prior studies have shown that applying the hub-and-spoke transportation organization mode to the CRExpress system could decrease operational cost effectively. To carry out network planning for CRExpress, based on its present situation and properties, a conventional hub location model is adjusted. The network planning location model for CRExpress which minimizes total operation cost and allows direct transportation mode is proposed as well as an algorithm based on the genetic algorithm (GA) approach. The reasonableness and feasibility of the model and algorithm are investigated and verified through a case study based on the CRExpress system. The result indicates that Chengdu, Yingkow, and Zhengzhou are selected as consolidation centers whereas Urumqi and Xining adopt direct transportation mode.